2017
DOI: 10.3168/jds.2016-11725
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of soybean oil supplementation on performance, digestion, and metabolism in dairy cows fed sugarcane-based diets

Abstract: We aimed to quantify the productive and metabolic responses, and digestive changes in dairy cows fed various concentrations of soybean oil (SBO) in high-concentrate, sugarcane-based diets. Eight rumen-cannulated multiparous Holstein cows in mid lactation (574 ± 19.1 kg of body weight and 122 ± 6.9 d in milk), averaging 22.5 ± 1.22 kg/d of milk were assigned to replicated 4 × 4 Latin squares. The experimental period lasted 21 d as follows: 14 d for adaptation, followed by a sampling period from d 15 to 21. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
2
12
1
Order By: Relevance
“…The negative effect of dietary inclusion of free vegetable oils on the milk fat content of cows is well documented in the literature (LOPES et al, 2015;RODRIGUES et al, 2017). In the present work, comparing the control ration with the 4.5% SO ration, this reduction was 14%.…”
Section: Itemsupporting
confidence: 67%
See 2 more Smart Citations
“…The negative effect of dietary inclusion of free vegetable oils on the milk fat content of cows is well documented in the literature (LOPES et al, 2015;RODRIGUES et al, 2017). In the present work, comparing the control ration with the 4.5% SO ration, this reduction was 14%.…”
Section: Itemsupporting
confidence: 67%
“…These results corroborate the linear reduction observed in the NDF ED (P=0.0358; Table 3) and, consequently, in the molar ratio of acetate (P=0.0741; Table 2). Moreover, the substitution of non-fibrous carbohydrates of the dietary ingredients by EE from the SO already promotes a decrease in fermentable substrate (RODRIGUES et al, 2017), limiting the development of the ruminal microbiota, which was indicated in the present study by the linear reduction in the excretion of purine derivatives (P=0.0127; Table 4). Corroborating this, negative correlations (P<0.05) of -0.69 and -0.59, were observed between the milk contents of the majority of the LECSFAs (i.e., C15:0 and C17:0) with EE intake.…”
Section: Indexmentioning
confidence: 62%
See 1 more Smart Citation
“…Supplementary fat characteristics and concentration in the diet dry matter (DM) are greatly determinant on its effects on rumen fermentation and fibre digestion (Palmquist, ; Weld & Armentano, ). Soya bean oil (SBO) is a high rumen release fat source rich in α‐linolenic acid (LNA; C 18:3 cis ‐9, cis ‐12, cis ‐15) which along with its main first biohydrogenation product; linoleic acid (LA; C18:2 cis ‐9, cis ‐12) has a known inhibitory effect on ruminal fibrinolytic bacteria, protozoa populations and fibre digestion (Rodrigues et al., ; Maia, Chaudhary, Figueres, & Wallace, ; Yang et al., ). Fatty acid (FA) composition and rumen release of supplementary fats, however, are not the only determinant factors for its effects on rumen fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Tropical environments have a wide range of heterogeneous forage species and diet formulation based on studies with non‐tropical forages can lead to inefficient diets. Sugarcane is a forage commonly fed to cattle in tropical environments, and it is often used as the main dietary fibre source (Daniel et al., ; Rodrigues et al., ). Mombaça guinea grass and Marandu palisadegrass are relevant forages for livestock production in Brazil and are widely used in grazing systems (Carvalho et al., ; Gimenes et al., ).…”
Section: Introductionmentioning
confidence: 99%